The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1964
DOI: 10.1083/jcb.22.3.565
|View full text |Cite
|
Sign up to set email alerts
|

Studies on an Epithelial (Gland) Cell Junction

Abstract: Membrane permeability of an epithelial cell junction (Drosophila salivary gland) was examined with intraccllular microclectrodes and with fluorescent tracers. In contrast to the non-junctional cell membrane surface, which has a low permeability to ions (I0 -4 mho/cm2), the junctional membranc surface is highly pcrmcable. In fact, it introduces no substantial restriction to ion flow beyond that in the cytoplasm; the resistance through a chain of cells (150 ~ cm) is only slightly greater than in extrudcd cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
0

Year Published

1966
1966
1999
1999

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 471 publications
(99 citation statements)
references
References 54 publications
7
92
0
Order By: Relevance
“…Just below this junction occurs the typical septate desmosome (Fig. 10) which has been known to be present in the wide phyla of invertebrates (WOOD, 1959, LOEWENSTEIN andKANNO, 1964;WIENER and LOEWENSTEIN, 1964;LOCKE, 1965). The septate desmosome is characterized by the presence of a septa across the interThe apical cytoplasm is particularly concentrated by abundant mitochondria.…”
Section: Epithelium Of the Hindgutmentioning
confidence: 99%
“…Just below this junction occurs the typical septate desmosome (Fig. 10) which has been known to be present in the wide phyla of invertebrates (WOOD, 1959, LOEWENSTEIN andKANNO, 1964;WIENER and LOEWENSTEIN, 1964;LOCKE, 1965). The septate desmosome is characterized by the presence of a septa across the interThe apical cytoplasm is particularly concentrated by abundant mitochondria.…”
Section: Epithelium Of the Hindgutmentioning
confidence: 99%
“…references 10,11,14), certain alternatives should be mentioned. The existence of a high resistance barrier surrounding the whole blastodisc is excluded since virtually no potential changes were recorded unless both current and recording micropipettes were intracellular.…”
Section: Discussionmentioning
confidence: 99%
“…certain nerve cells, cardiac, and visceral muscle cells) (1,2,4,5), but also between certain nonexcitable cells (e.g. glial cells and epithelial cells in insects, amphibians, and mammals) (8)(9)(10)(11)13). In all the cases cited above, electron microscopy has shown that the cells are connected by regions of specialized membrane apposition (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probe was microinjected into individual cells (23,31), and the fraction of first-order neighbors displaying LRB-Glu fluorescence within 5 min of the injection-the incidence of permeable interfaces-was scored. In all cases analyzed, including the transformed condition, the first-order neighbors could be clearly distinguished; regions with excessive cell overlap were not used.…”
mentioning
confidence: 99%